2016
DOI: 10.4012/dmj.2015-341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal cyclic stress on acid resistance of resin-infiltrated incipient enamel lesions <i>in vitro </i>

Abstract: This study aimed to examine the effect of thermal cycling on gap formation at the interface between infiltrated resin (ICON ® ) and enamel lesion and on the durability of anti-demineralization efficacy to predict the future performance. SS-OCT technique was examined to determine whether it has the potential to detect the gap. Bovine enamel lesions were prepared, and the infiltrated resin was applied to the lesion. Resin-infiltrated lesion specimens were thermal cycled 10,000 cycles and further demineralized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(44 reference statements)
2
4
0
1
Order By: Relevance
“…34 Ourcolor results came in agreement with those of Bak et al 25 and Yetkiner et al 35 who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies [36][37][38][39][40] which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches [41][42][43] which reported that surface roughness and color stability of resin-infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment.…”
Section: Discussionsupporting
confidence: 91%
“…34 Ourcolor results came in agreement with those of Bak et al 25 and Yetkiner et al 35 who proved the ability of resin infiltrant to resist thermal and discoloration challenges. Regarding surface roughness, our results agreed with previous studies [36][37][38][39][40] which concluded that resin infiltration of enamel lesions can provide and maintain smoother surface. However, these results contrast those of other researches [41][42][43] which reported that surface roughness and color stability of resin-infiltrated enamel lesions were less than ideal and could further recede with aging in the oral environment.…”
Section: Discussionsupporting
confidence: 91%
“…The increased surface roughness observed on the resin-infiltrated lesions with aging in the present study, may be attributed to internal and thermal stresses generated by water sorption and thermal expansion and contraction. 19 The present results agreed with former studies [30][31][32] which reported the ability of resin infiltrants to provide and maintain smoother enamel surface. However, other studies 19,33,34 came in contrast, as they reported that surface roughness of resin-treated enamel lesions were not ideal and might further recede with aging.…”
Section: Discussionsupporting
confidence: 92%
“…A longer experiment that mimics 5 years of in vivo conditions might deliver more accurate results about the long-term stability of the infiltrate. In other studies, infiltrated lesions were subjected to thermocycling combined with acid challenges to test the surface stability [ 10 , 39 ]. The results of these studies were similar to the findings in this study.…”
Section: Discussionmentioning
confidence: 99%